2014
DOI: 10.1186/1476-7120-12-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food intake on left ventricular wall stress

Abstract: ObjectiveLeft ventricular wall stress has been investigated in a variety of populations, but the effect of food intake has not been evaluated. We assessed whether left ventricular wall stress is affected by food intake in healthy subjects.MethodsTwenty-three healthy subjects aged 25.6 ± 4.5 years were investigated. Meridional end-systolic wall stress (ESS) and circumferential end-systolic wall stress (cESS) were measured before, 30 minutes after, and 110 minutes after a standardised meal.ResultsBoth ESS and cE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Our study population has previously been evaluated in other published reports (Dencker et al ., ; Hlebowicz et al ., ,b; Gårdinger et al ., ). Nineteen healthy subjects, aged 26·2 ± 4·2 years, were investigated.…”
Section: Methodsmentioning
confidence: 97%
“…Our study population has previously been evaluated in other published reports (Dencker et al ., ; Hlebowicz et al ., ,b; Gårdinger et al ., ). Nineteen healthy subjects, aged 26·2 ± 4·2 years, were investigated.…”
Section: Methodsmentioning
confidence: 97%
“…There is a continuous search for novel biomarkers that could improve the assessment in neurological diseases (Lind et al., ; Lind, Emami Khoonsari et al., ; Lind, Wu et al., ; Miclescu, Svahn, & Gordh, ; Moen et al., ). Digestion of food is known to have significant hemodynamic and metabolic effects (Dencker, Björgell, & Hlebowicz, ; Dieden, Gårdinger, Bjorgell, Hlebowicz, & Dencker, ; Gårdinger, Bjorgell, Hlebowicz, & Dencker, ; Hlebowicz, Lindstedt‐Ingemansson, Björgell, & Dencker, ; Hlebowicz, Lindstedt‐Ingemansson, Björgell, & Dencker, ; Quatela, Callister, Patterson, & MacDonald‐Wicks, ; Stensel, ), and may therefore affect different biomarkers. It is relevant from a practical point of view to investigate if these biomarkers are affected by food intake, as it would affect sample collection.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Digestion of food is known to alter hemodynamics, [5][6][7] and we have previously shown that both systolic and diastolic functions are affected significantly when comparing echocardiographic exams during fasting and after a meal in a young population. [8][9][10][11] Though the findings might not be of consequence for clinical evaluations in everyday practice, they suggest that the effects of food consumption should be considered, in studies, especially if the sample size is small. [8][9][10][11] The cardiovascular system changes with increasing age, both physiologically and not so rarely pathologically.…”
Section: Introductionmentioning
confidence: 94%
“…[8][9][10][11] Though the findings might not be of consequence for clinical evaluations in everyday practice, they suggest that the effects of food consumption should be considered, in studies, especially if the sample size is small. [8][9][10][11] The cardiovascular system changes with increasing age, both physiologically and not so rarely pathologically. [12][13][14][15][16] Hence, senior people are an important target group in cardiovascular studies.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation